Impact of MAPWA Programme on Empowerment of the Beneficiaries in Madhya Pradesh (Indian Journal of Extension Education, 2012)
The study was conducted in Katni district of Madhya Pradesh with 240 beneficiaries under Madhya Pradesh Women in Agriculture (MAPWA) programme to know its impact in the course of knowledge, adoption and economic viability of low-cost technologies/practices used by farm women. The study revealed that majority of the small landholding farm women were found under the category of low level of adoption while, in medium landholding category, majority had medium level of adoption. The results of economic viability showed that all the skills have responded remarkably in terms of yield and returns under irrigated and rainfed condition. Thus all the skills are highly remunerative and econo-mically viable. Hence MAPWAproject is advised to include all these skills in its development programme on the priority basis for increasing the agricultural productivity. The findings could be helpful to extension workers and policy-makers in developing and intensifying the dissemination of these technologies among the farmers of both rainfed and irrigated conditions.